2005
DOI: 10.1002/ejoc.200500031
|View full text |Cite
|
Sign up to set email alerts
|

A New Glucose: Towards Conformationally Locked Hexoses through Annulation

Abstract: A new family of surface-modified carbohydrates with locked, axial-rich conformations and bipolarofacial architectures has been developed with the aid of carbocyclic ring annulation. These novel trans-decalin-based carbohydrates have been synthesized, from simple aromatic precursors such as tetralin, through the ozonolysis of an appropriately protected allylic alcohol, followed by a cascade of intramolecular acetalizations to generate the sugar pyran moiety. The stereoselective synthesis of (racemic) cyclohexan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Data for α-15: mp 61−64 °C; (16). To a stirred solution of diol 15 (172 mg, 440 μmol) and NaH (60% in mineral oil, 120 mg; 72 mg of NaH, 3.0 mmol) in DMF (8.0 mL) was added BnBr (301 mg, 1.76 mmol) at rt.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data for α-15: mp 61−64 °C; (16). To a stirred solution of diol 15 (172 mg, 440 μmol) and NaH (60% in mineral oil, 120 mg; 72 mg of NaH, 3.0 mmol) in DMF (8.0 mL) was added BnBr (301 mg, 1.76 mmol) at rt.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Realization of advanced and stable stereoselectivity in chemical glycosylation has been a fundamental challenge for synthetic organic chemists for many years. Among the variety of methods for realizing stereoselectivity, stereocontrol on the basis of conformational locking of pyranose rings is one developing area of research, Theoretical calculations have also indicated the significance of the conformational control. Locking the conformation to the inverted form of pyranose rings has been a typical approach. Ring inversion produces carbohydrates possessing more axial substituents, which are called axial-rich forms. To lock a conformation into an axial-rich form, steric repulsion between bulky silyl groups has often been applied. , The axial-rich form has enhanced the reactivity of glycosyl donors. , In contrast, a reduction in reactivity , and migration of the silyl groups due to their intense steric hindrance have also been observed in some instances, which suggests a brittleness of the locking method of conformation.…”
mentioning
confidence: 99%
“…1). [12] Such ground-state axial-rich conformations of hydroxy groups were subsequently observed in various intermediates and end products, obtained along synthetic routes devised by our group for annulated hexoses 8, [15] inosito-inositols 9 [16] and conjoined inositols 10 (Fig 2). [17] In each of these synthetic endeavors, the 9,10-dihydroxy-trans-decalin framework could be reliably employed as a prototypical path for locking the hydroxy substituents in spatial orientations which might not have been realized otherwise.…”
Section: Supramolecularmentioning
confidence: 69%
“…7 It would also be worth referring at this point to the crystal packing of raccyclohexa-annulated methyl-a-gulopyranoside, which like 1 and 2, shows a columnar architecture with a hydrophilic interior and a hydrophobic exterior. 26 This head-to-head bilayer molecular assembly disappears completely in cyclopenta-annulated 4, which shows a crystal packing, more akin to that of a hydrophilic inositol. The current study provides therefore a direct demonstration of the potential ability of cycloalkane annulation to serve as a tool in fine-tuning the…”
Section: Discussionmentioning
confidence: 95%